1994
DOI: 10.2165/00003088-199426030-00002
|View full text |Cite
|
Sign up to set email alerts
|

Ceftibuten Pharmacokinetics and Pharmacodynamics

Abstract: Ceftibuten is an extended-spectrum, cephem antimicrobial agent formulated for oral administration. Ceftibuten is absorbed by carrier-mediated processes and passive diffusion. The absorption of ceftibuten is described adequately by a first-order process. Following oral administration, peak serum ceftibuten concentrations are reached within 2 to 3 hours. Although the absolute bioavailability of ceftibuten in humans is not known, its relative bioavailability indicates that there is relatively rapid and complete a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…In vitro synergism has been demonstrated between paclitaxel and hydroperoxyifosfamide, an activated ifosfamide metabolite, against cisplatinsensitive and -resistant Ovarian Carcinoma cell lines when paclitaxel preceded hydroperoxy-ifosfamide or during concurrent exposure (Liebmann et al, 1994;Klaassen et al, 1996). Based on these preclinical in vitro experimental data, we believe that the sequence and infusion times regarding docetaxel and ifosfamide, as applied in the present study, might lead to potential in vivo synergism between these two drugs (Kearns et al, 1995). Moreover, our prior experience with paclitaxel -ifosfamidecisplatin (Kosmas et al, 2000a, b;2001) or docetaxel -ifosfamide -cisplatin (Kosmas et al, 2002) combinations has demonstrated their feasibility in phase I and phase II studies in advanced solid tumours and lung cancer in particular.…”
Section: Discussionmentioning
confidence: 58%
“…In vitro synergism has been demonstrated between paclitaxel and hydroperoxyifosfamide, an activated ifosfamide metabolite, against cisplatinsensitive and -resistant Ovarian Carcinoma cell lines when paclitaxel preceded hydroperoxy-ifosfamide or during concurrent exposure (Liebmann et al, 1994;Klaassen et al, 1996). Based on these preclinical in vitro experimental data, we believe that the sequence and infusion times regarding docetaxel and ifosfamide, as applied in the present study, might lead to potential in vivo synergism between these two drugs (Kearns et al, 1995). Moreover, our prior experience with paclitaxel -ifosfamidecisplatin (Kosmas et al, 2000a, b;2001) or docetaxel -ifosfamide -cisplatin (Kosmas et al, 2002) combinations has demonstrated their feasibility in phase I and phase II studies in advanced solid tumours and lung cancer in particular.…”
Section: Discussionmentioning
confidence: 58%
“…This study has demonstrated the feasibility of two oral schedules of Ro 31-7453 with an acceptable safety profile. In addition, the current available pharmacokinetic data compare favorably with the nonlinear kinetics of Vinca alkaloids (14,15) and paclitaxel (16). The 14-day schedule of oral Ro 31-7453 at the recommended dose of 125 mg/m 2 bid is being evaluated in Phase II trials in patients with breast, lung, and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A nonlinear pharmacokinetic model with Michaelis-Menten kinetics at distribution and elimination processes was suggested for paclitaxel. 7,17) However, we used the linear model because the difference in the AUC between the nonlinear and the linear models was minimal and because the linear model is easier than the nonlinear model to handle in pharmacodynamic analysis. 15) Pharmacodynamic study The entire time course of leukopenia after treatment with paclitaxel was fitted in each patient by using a pharmacodynamic model which we have recently developed.…”
Section: Patientsmentioning
confidence: 99%